DEVELOPING DIGITAL AUDIO DESCRIPTION TO HEALTH KNOWLEDGE PROMOTION ON OVER-THE-TOP TELEVISION USING IMAGINEERING PROCESS - Maneehaet, Sirodom (Journal of MCU Nakhondhat, 2024)
The purposes of this research were to 1) develop a digital audio description to health knowledge promotion on over-the-top television using imagineering process, 2) study of health knowledge after exposure to digital audio description, and 3) study of receivers' satisfaction with digital audio description. This work used a mixed methods research method. It is a quantitative study plan that collects data using questionnaires and then uses the data for analysis. Along with qualitative study, data is collected using interviews and focus groups and then analyzed. The target group of the research was selected by purposive sampling, 20 vision impaired people registered in the Udon Thani Municipality area. The research tools were 1) a digital audio description to health knowledge promotion on over-the-top television using imagineering process, 2) the test of health knowledge after exposure to digital audio description to health knowledge promotion, and 3) the questionnaires of receivers' satisfaction with digital audio description to health knowledge promotion by the consistency of each question with the research objectives is not less than 0.67. The results of the research revealed that 1) the process of develop a digital audio description to health knowledge promotion on over-the-top television using imagineering process, divided into 6 aspects: imagine step, study step, design and develop step, present step, improve step, and evaluate step, 2) the 80 percent of the receivers were able to health knowledge more than criteria standards after exposure to digital audio description was at a high level, and 3) the level of satisfaction of the receivers for a digital audio description to health knowledge promotion on over-the-top television using imagineering process was at a highest level (Mean = 4.51, S.D. = 0.64).